2000
DOI: 10.1007/pl00002331
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Hemoglobin Concentrations in Patients with Advanced Head and Neck Cancer Treated with Combined Radio-Chemotherapy and Surgery

Abstract: In our study hemoglobin level after radio-chemotherapy was identified for the first time to be also a significant prognostic factor (univariate analysis) in head and neck cancer patients who underwent combined radio-chemotherapy. Besides chemotherapy plus low-dose irradiation achieved similar results in comparison with radical resection and high-dose radiotherapy at least for the first 2 years after therapy. Relapsing disease could be treated with 1 additional course of radiotherapy which is supposed to be wel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
(40 reference statements)
0
16
0
2
Order By: Relevance
“…Several studies of head and neck carcinomas have also reported the negative effects of a decrease in Hb levels during or after radiotherapy. [23][24][25] Therefore, when the prognostic value of Hb level is being evaluated in patients treated with sequential chemoradiotherapy, midradiation Hb levels are a more reliable indicator of anemia than are pretreatment levels and thus should also be monitored. Nonetheless, the current study does not exclude the possibility that preradiation Hb level is also a useful prognostic factor for patients with NPC, as only a limited number of patients treated with radiotherapy alone had preradiation Hb levels that were less than the threshold value.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of head and neck carcinomas have also reported the negative effects of a decrease in Hb levels during or after radiotherapy. [23][24][25] Therefore, when the prognostic value of Hb level is being evaluated in patients treated with sequential chemoradiotherapy, midradiation Hb levels are a more reliable indicator of anemia than are pretreatment levels and thus should also be monitored. Nonetheless, the current study does not exclude the possibility that preradiation Hb level is also a useful prognostic factor for patients with NPC, as only a limited number of patients treated with radiotherapy alone had preradiation Hb levels that were less than the threshold value.…”
Section: Discussionmentioning
confidence: 99%
“…Whether Hb levels at the start of therapy (or at presentation, e.g., [14,22,25,28,46,62]), at the nadir during therapy (e.g., [26,81]), at the peak during therapy (e.g., [41]), or at the end of (radio)therapy (e.g., [81,94]) are of prognostic value in terms of better disease-free and overall survival is still being assessed in ongoing studies.…”
Section: Tumor Hypoxia and Anemia As Adverse Prognostic Factorsmentioning
confidence: 99%
“…Radiotherapy alone versus surgery alone can only be compared indirectly since there are no randomized clinical trials. Controlled clinical trials do not show any survival bene t for patients treated postoperatively with 30 Gy (27) or [49][50][51][52][53][54][55][56]29). Radiotherapy can thus not be recommended as a single modality treatment or as the only adjuvant therapy with surgery in a curative approach.…”
Section: Radiotherapymentioning
confidence: 99%
“…Both cisplatin and 5-FU seem to be synergistic with radiation. There is also less risk of accelerated repopulation of tumor cells during treatment, which is an important cause of local failure in cancer of the head and neck (49) and cervix (50). Even if the acute esophageal toxicity is greater with the concurrent treatment, late toxicity seems to remain the same (51,11).…”
Section: Non-surgical Treatmentmentioning
confidence: 99%